URGENSI KAUMAN MENARA KUDUS SEBAGAI CAGAR BUDAYA ISLAM - Moh Rosyid (Fakultas Seni Rupa dan Desain ITB, 2019)
There are many historical sites in Kauman areas in Kudus: al-Aqsha Mosque, the Minaret, Bringin Park, Madureksan Mosque, the Tomb of Sunan Kudus, the House of Sunan Kudus, madrasas and boarding schools. The government of Kudus needs to pay more attention to the reservation of Kauman areas. In the beginning of 2016, the government has completed the renovation of Bringin Park in between Madureksan Mosque and Hok Ling Bio temple. Obviously, Kaumans is rich of historical sites. The government is expected to establish a museum, to relocate merchandise stores in fornt of Al-Aqsha Mosque, to select a professional team for the heritage preservation and to revilatize the legacy of Sunan Kudus.